1996
DOI: 10.1089/neu.1996.13.465
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Local Microvascular Permeability and in the Effect of Intervention with 21-Aminosteroid (Tirilazad) in a New Experimental Model of Focal Cortical Injury in the Rat

Abstract: In a new, reproducible model of rodent focal cortical injury, we have shown that in the absence of early traumatic disruption of the microvasculature and subsequent hemorrhage, delayed perivascular protein leakage and polymorphonuclear leukocyte infiltration of the injured cortex occur. In this study we employed a sensitive quantitative autoradiographic technique (using alpha-aminoisobutyric acid as a tracer) to investigate the focal changes in microvascular permeability with time and to determine the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The main previous studies of injury–induced CNS barrier dysfunction to small molecules are those of Hartl et al . (1997) in rabbits following brain injury, Mathew et al . (1996) in rats following brain injury and Popovich et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main previous studies of injury–induced CNS barrier dysfunction to small molecules are those of Hartl et al . (1997) in rabbits following brain injury, Mathew et al . (1996) in rats following brain injury and Popovich et al .…”
Section: Discussionmentioning
confidence: 98%
“…(1997) reported increased visible extravasation of Na‐fluorescein (385 Da) from pial blood vessels on the surface of the brain in rabbits 1 h after a fluid percussion injury, but by 6 h postinjury the fluorescein was already confined to the vessel lumen (these authors did not investigate later time points or other times between 1 and 6 h). Mathew et al . (1996) and Popovich et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of the significantly increased BBB permeability at 4 h post trauma is in accordance with a previous report that the barrier leakage to a-aminoisobutyric acid peaks at 4 h after a focal cortical contusion. 44 The elevation of the BBB permeability between 1 and 4 h following injury might be due to further damage of the disrupted barrier post trauma, which is caused by the ischemia right after TBI, 44 or the greater surface area of the leaky BBB induced by the higher perfusion of the disrupted vessels via the above mentioned bypass.…”
Section: Cerebral Microvascular Responses In Injured Brain Y Lin Et Almentioning
confidence: 99%
“…This is not surprising, given tirilazad's demonstrated efficacy in animal models of head injury, subarachnoid hemorrhage (SAH) and cerebral ischemia (Smith et al, 1994;Hall, 1996Hall, , 1997. Tirilazad has been shown to attenuate the post-injury rise in cortical «OH levels and to protect the blood-brain barrier (BBB) following impact injury in the rat and mouse Smith et al, 1994;Mathew et al, 1996), and to improve microvascular hypoperfusion as well as decrease BBB damage, edema, and delayed vasospasm in SAH (Hall and Travis, 1988a;Zuccarello and Anderson, 1989;Hall, 1996). We have also reported that a signifi-cant loss of cortical tissue, indicative of progressive neuronal degeneration, occurs in shaken infant rats 7-14 days post-injury (Smith et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Blood-brain barrier damage has also been observed following the intraventricular infusion of NMDA in rats (Dietrich et al, 1992). NMDA receptor antagonists and glutamate release inhibitors, on the other hand, have been shown to decrease edema and infarct volume following head injury and hypoxia-ischemia in both neonatal (McDonald and Johnston, 1990; and adult rats (Mclntosh et al, 1990;Povlishock, 1993;Wahl et al, 1996;Du et al, 1996). Similarly, BBB damage is reportedly reduced following transient focal ischemia in adult rats pretreated with the NMDA antagonists, MK-801 or dextrorphan (Yang et al, 1994;Du et al, 1996).…”
Section: Introductionmentioning
confidence: 99%